COMPARATIVE ANALYSIS OF SYNTACTIC COMPLEXITY IN INDONESIAN GRADUATE-LEVEL WRITING: A CORPUS STUDY OF MASTER'S THESES VERSUS DOCTORAL DISSERTATIONS - Anjarwati, Dhini; Basthomi, Yazid; Zen, Evynurul Lailiy (English Review: Journal of English Education, 2024)
Syntactic complexity is an essential indicator of English Foreign Language (EFL) students' academic writing quality. Previous studies analyzed and compared syntactic complexity in published research articles through large-grained measures. However, the study of syntactic complexity unpublished research at graduate level gains less attentions. Thus, this study tried to fill the gap by analyzing and comparing syntactic complexity of master theses and doctoral dissertations that written by Indonesian students through fine-grained measures. This study conducted a quantitative design of a corpus-based method. The corpus data consists of two sub-corpora that selected through stratified sampling technique based on years and issues. Those were 52 doctoral dissertations and 74 master theses from English Language Education of Universitas Negeri Malang. The twelve phrasal complexity measures were employed through Tool for the Automatic Analysis of Syntactic Sophistication and Complexity (TAASSC) tool created by Kyle (2016). The finding showed the characteristics of Indonesian graduate-level writing that they were intended to utilize more dependents per direct object (standard deviation) measures, and fewer dependents per nominal (standard deviation) measures in their writing. It also showed doctoral dissertations have higher quality than master theses which reflected significant difference in most of phrasal complexity measures. These outcomes offer syntactic complexity insights of Indonesian context. The study highlighted the need more attention to syntactic complexity at graduate-level writing for improving writing quality.